A point of view on genetic resources and plant breeding - Escandon, Alejandro Salvio (Sociedade Brasileira de Floricultura e Plantas Ornamentais, 2022)
Biodiversity is the set of living organisms that make up our battered planet and their interactions with the environment. It is made up of the Kingdoms: Animalia, Plantae, Fungi, Protista, and Monera. It provides the energy resources necessary to sustain the planet and our civilization; it is the basis of agriculture, source of all crops, and species of domestic livestock since the beginning of human civilization.